2017
DOI: 10.1530/eje-17-0340
|View full text |Cite
|
Sign up to set email alerts
|

Higher glucocorticoid replacement doses are associated with increased mortality in patients with pituitary adenoma

Abstract: Patients with NFPA and AI receiving more than 20 mg HCeq per day have an increased mortality. Our data also show that mortality in patients substituted with 20 mg HCeq per day or less is not increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 29 publications
0
38
0
2
Order By: Relevance
“…As an endocrinologist, the aim is to use 20 mg of hydrocortisone daily as a replacement dose for patients with adrenal insufficiency, although the daily doses may be much higher when you are treating other diseases. 7,35 The definition of prednisolone equivalent dose in our inclusion criteria differs from the DDD definition. Betamethasone causes more profound suppression of the hypothalamic-pituitary-adrenal axis than an equivalent anti-inflammatory dose of prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…As an endocrinologist, the aim is to use 20 mg of hydrocortisone daily as a replacement dose for patients with adrenal insufficiency, although the daily doses may be much higher when you are treating other diseases. 7,35 The definition of prednisolone equivalent dose in our inclusion criteria differs from the DDD definition. Betamethasone causes more profound suppression of the hypothalamic-pituitary-adrenal axis than an equivalent anti-inflammatory dose of prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that conventional GC replacement therapy is associated with reduced life expectancy and increased morbidity in patients with AI, compared to the general population . In a recent survey on 1281 participants, conventional GC treatment was demonstrated to be associated with impaired quality of life, fatigue, high absenteeism from work or school and a high rate of hospitalization for adrenal crises, vomiting or acute infections .…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic hyponatraemia secondary to ACTH deficiency may be identified at presentation with CP . ACTH deficiency and higher dose of hydrocortisone replacement therapy (>25 mg/d in acromegaly; >20 mg/d in NFPA patients) in other pituitary disorders are associated with increased mortality, but these associations have not been studied specifically in CP cohorts . In studies using cortisol day curves, hydrocortisone doses of 10 mg in the morning and 5 mg in the early afternoon were the best approximation to physiological replacement in adult patients; however, there is no outcome‐based research in support of any one hydrocortisone dose at present …”
Section: Anterior Pituitary Dysfunctionmentioning
confidence: 99%